The Comparison between Individual and Collaborative Writing on Narrative Paragraphs Achievement - Khairunnas Syafi’i (Indonesian Journal of Integrated English Language Teaching, 2016)
The main objective of the study was to find out the difference of writing on narrative paragraphs achievement between students writing individually and collaboratively.  This study was a comparative research which was intended to find out the difference between individual and collaborative writing narrative paragraphs achievement.  The participants of the study comprised 54 students found in 2 classes randomized from eight classes.  Individual writing was implemented on the first class (n=30) and collaborative writing was implemented on the second class (n=30).  Data were collected using writing test.  Quantitative data were analyzed using descriptive and inferential statistics.  The findings showed that there was a significant difference between Individual and Collaborative Writing on Narrative Paragraphs Achievement of the Second Year Students at MAN 1 Pekanbaru.